2020
DOI: 10.1002/jhbp.822
|View full text |Cite
|
Sign up to set email alerts
|

Small‐for‐size graft, small‐for‐size syndrome and inflow modulation in living donor liver transplantation

Abstract: The extended application of living donor liver transplantation (LDLT) has revealed the problem of graft size mismatching called "small-for-size syndrome (SFSS)." The initial trials to resolve this problem involved increasing the procured graft size, from left to right, and even extending to include a right lobe graft. Clinical cases of living right lobe donations have been reported since then, drawing attention to the risks of increasing the liver volume procured from a living donor. However, not only other mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 113 publications
0
21
0
Order By: Relevance
“…Donor safety, remnant liver volume for the donor, and graft volume for the recipient are the major concerns and dilemmas for living donor liver transplant however published studies showed favorable results and minor concerns. [8][9][10] Lee JG et al published a study from Korea, they performed living donor liver transplant without MHV in the majority of their cases and showed that donor hepatectomy can be performed successfully with minor morbidity and easily controlled complications, the biliary complications were the most common major complication, they didn't find a statistical difference in laboratory results or complication between the donor with RLV less than 30% and those with RLV of more than 30%. [12] In this study, we had one donor with a major biliary leak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor safety, remnant liver volume for the donor, and graft volume for the recipient are the major concerns and dilemmas for living donor liver transplant however published studies showed favorable results and minor concerns. [8][9][10] Lee JG et al published a study from Korea, they performed living donor liver transplant without MHV in the majority of their cases and showed that donor hepatectomy can be performed successfully with minor morbidity and easily controlled complications, the biliary complications were the most common major complication, they didn't find a statistical difference in laboratory results or complication between the donor with RLV less than 30% and those with RLV of more than 30%. [12] In this study, we had one donor with a major biliary leak.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Using the right liver lobe and because of higher parenchymal volume would mitigate these injuries but donor safety has always been questioned when MHV is incorporated. [8][9][10] Doppler US can be used postoperatively for the detection of vascular complications in liver transplants. [11] In this retrospective study, the middle hepatic vein was used in live donor liver transplantation and the venous outflow dynamics was studied immediately after transplant meanwhile we studied the impact of the graft function on donor functionality and overall donor safety.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies measuring the weight of the liver graft at each step of the back-table procedure are required. Third, the ratio of graft volume (GV) to standard liver volume (SLV), which is another concept used to evaluate graft size for a recipient, was not considered in this study [ 32 , 33 ]. Urata et al demonstrated that the conversion ratio for liver weight and liver volume was 1.12 g/mL, rather than 1.0 g/mL [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with clinical scenarios, due to individual differences, when the volume of the liver is removed beyond a certain threshold, the remaining liver regeneration function declines, eventually leading to the inevitable occurrence of liver failure ( Ikegami et al, 2020a ). Therefore, the study of 90% hepatectomy mouse models provides an ideal and important means for the further clarification of the pathogenesis of SFSS, as well as screening of different liver support systems for SFSS ( Dili et al, 2019 ; Ikegami et al, 2020b ) ( Table 1 ).…”
Section: Mouse Models Of Acute Liver Injurymentioning
confidence: 99%